1991
DOI: 10.1128/jcm.29.7.1530-1532.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive antibodies induced by a monovalent influenza B virus vaccine

Abstract: Influenza viruses related to the markedly antigenically divergent strains B/Yamagata/16/88 and B/Victoria/ 2/87 are circulating in human populations. Adults develop cross-reacting antibodies against recent and earlier influenza B virus strains after vaccination with B/Yamagata/16/88, probably because of previous influenza B virus infections or immunizations. Vaccines containing B/Yamagata/16/88 should adequately protect adults against B/Victoria/2/87 infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 8 publications
2
17
0
4
Order By: Relevance
“…Ferrets infected with an IBV from one lineage has antibodies with HAI activity against both the infecting virus, but also strains from the opposite lineage, as well as the pre-split, B/ Lee/40 IBV. [16][17][18][19][20] Therefore, younger subjects born decades after the lineage split in 1987 may have cross-reactive antibodies to these older IBV strains. This phenomenon was observed in this study during the 2014-2015 season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferrets infected with an IBV from one lineage has antibodies with HAI activity against both the infecting virus, but also strains from the opposite lineage, as well as the pre-split, B/ Lee/40 IBV. [16][17][18][19][20] Therefore, younger subjects born decades after the lineage split in 1987 may have cross-reactive antibodies to these older IBV strains. This phenomenon was observed in this study during the 2014-2015 season.…”
Section: Discussionmentioning
confidence: 99%
“…However, immunological priming is often needed for this cross-reactive binding. [19][20][21] Previous exposures to IBV via infection or vaccination is most effective in the elicitation of cross-protective antibodies. This is especially the case with the Victoria lineage where studies have shown that children without detectable antibodies against Victoria-lineage strains prior to vaccination failed to exhibit a rise in these antibodies following vaccination with TIV vaccines containing only a Yamagata strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to FluA, the vast majority of antibody responses against Although the two lineages are considered antigenically distinct, HA-directed antibody cross-reactivity between the two lineages has been observed in various contexts [111][112][113][114][115] potentially due to original antigenic sin [116].…”
Section: Antibody Responsesmentioning
confidence: 99%
“…En todas las cohortes se observó seroconversión heteróloga frente al linaje de gripe B no incluido en la vacuna en dicha temporada, en porcentajes que fueron desde el 4% al 11% frente al linaje B/Yamagata cuando era el B/Victoria el que estaba incluido en la vacuna, y del 9% frente al linaje B/Victoria en la cohorte vacunada con el linaje B/Yamagata. Estos valores demuestran una cierta respuesta humoral heterotípica entre ambos linajes de gripe B que ya ha sido descrita en otros trabajos científicos (122,(231)(232)(233). Pese a que esta respuesta heteróloga no parece ser muy común y existe limitada información científica sobre el tema, sí que existen trabajos donde se ha demostrado protección cruzada en vacunados con linaje B/Yamagata frente a infecciones por linajes B/Victoria, hecho que no parece suceder en el sentido opuesto (233).…”
Section: Estudio De La Respuesta Inmune Humoral a La Vacuna Trivalentunclassified